Bimbingan Agama Dalam Mengurangi Stress Akademik Anak Di Masa Pandemi - Dika Sahputra (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2021)
This research is motivated by the existence of student academic stress during the pandemic. One of the efforts made in reducing academic stress is with religious guidance carried out by parents. The purpose of this study was to see the religious guidance carried out by parents in reducing children's academic stress during the pandemic. The research method is qualitative. Data were collected through interviews and observations. Data is analyzed by data triangulation (collecting, reducing, and concluding data). The results of this study are that the religious guidance carried out by parents in reducing children's academic stress is with moral, faith, worship, personal, social, and academic guidance.